2012
DOI: 10.1111/j.1600-6143.2012.04236.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Survivors of Kidney Transplantation

Abstract: There have been few studies of patients with renal allografts functioning for more than 20 years. We sought to identify clinical factors associated with ultra longterm (>20 year) renal allograft survival and to describe the clinical features of these patients. Comorbidities included skin cancer (36.1%), coronary heart disease (17.3%) and other malignancies (14.5%). This study identifies factors associated with long-term allograft survival and a high rate of morbidity and early mortality in long-term transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 14 publications
6
53
0
2
Order By: Relevance
“…The authors concluded that in these long-term kidney graft survivals, the focus of management should be on the prevention of cancers and CVD, as the prevalence was very high in these patients. In another study, the most common causes of death among KTRs 20 years after transplantation were CVD and malignancy [21]. As with our study, a higher incidence of cancer and CVD was found among 2,202 KTRs even 10 years after transplantation [22].…”
Section: Discussionsupporting
confidence: 73%
“…The authors concluded that in these long-term kidney graft survivals, the focus of management should be on the prevention of cancers and CVD, as the prevalence was very high in these patients. In another study, the most common causes of death among KTRs 20 years after transplantation were CVD and malignancy [21]. As with our study, a higher incidence of cancer and CVD was found among 2,202 KTRs even 10 years after transplantation [22].…”
Section: Discussionsupporting
confidence: 73%
“…Advancements in renal transplantation over the past 3 decades have widened access to transplantation for individuals with end-stage renal disease and improved both graft and recipient survival (1,2). The growing population of RTRs on the Island of Ireland, therefore, requires surveillance to detect when any new aspect of clinical management poses a risk factor for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compared with the 5-year survivals (70-80%) of other organs (kidney, islet, heart, etc.) [45][46][47], the survival of corneal allotransplantation is not high, except in patients with keratoconus. The patient with corneal blindness does not have any option except transplantation.…”
Section: Quality Control Of Porcine Corneal Productsmentioning
confidence: 99%